Pregnancy outcome and Ebstein's anomaly. - Donnelly, J E (1991)
BACKGROUND--Ebstein's anomaly is an uncommon congenital cardiac abnormality that may be associated with cyanosis and arrhythmias. For those female patients with the anomaly who survive to adult life there is little information available about pregnancy, maternal complications, and fetal outcome. This study was designed to address this issue so that these patients can receive appropriate advice and management. METHODS AND RESULTS--Forty two pregnancies in 12 women with Ebstein's anomaly were studied. The mothers' cardiac lesions were assessed on the basis of symptoms, the presence of cyanosis or arrhythmia, and by echocardiographic grading of severity. In the absence of important maternal cyanosis or arrhythmia, pregnancy was well tolerated. Neonatal outcome was good though there was an increased risk of prematurity and dysmaturity in the babies born to mothers with cyanosis. CONCLUSIONS--This study indicates that women with Ebstein's anomaly who reach child-bearing age can be advised that pregnancy is likely to be well tolerated with good fetal outcome. Maternal arrhythmia or cyanosis are indications for closer maternal and fetal observation.